(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background and aim: Central venous catheters (CVC) are widely used in critical care units. Due to the high prevalence of central venous catheter dysfunction, the cost, and the complications of their replacement, finding the right way to prevent catheter occlusion becomes important. The current study aimed to evaluate the effect of an intermediate dose of heparin solution in the prevention of central venous catheter occlusion in ICU-admitted patients.Method: This randomized controlled trial was performed in the Adult Intensive Care Unit (AICU) of Imam Reza Hospital from 2019 to 2020. In each patient (153 patients), the lines were divided into two categories: active or inactive. Inactive lines in the intervention group (76 patients) were washed every 8 hours with 10 ml of saline solution and then filled with 1.5 ml of heparin solution (at a concentration of 100 units per ml). In the control group (77 patients) only washing with 10 ml of saline solution was performed. The active lines in the intervention group were first washed with 10 ml of saline solution after each use and filled with 1.5 ml of heparin solution if not used immediately. In the control group, only saline washing was performed. Each line was examined once daily during the morning shift to determine whether it was open or closed.Result: In the studied lines in 153 patients admitted to the intensive care unit who were divided into two groups of intervention (heparin) and control (saline), no significant difference was observed in the occlusion of the catheter lines (p>0.05).Conclusion: After 14 days of examination of central venous catheters in patients, the effectiveness of an intermediate dose of heparin in preventing catheter obstruction was not more than the saline solution.